Sistem Informasi Pendaftaran Nikah Pada KUA Kecamatan Semidang Alas Berbasis Web - Melanisma Yunita; Indra Kanedi; Venny Novita Sari (UNIVED Press, 2025)
The Religious Affairs Office (KUA) of Semidang Alas Sub-district is one of the religious affairs offices located in Seluma Regency, Bengkulu Province. However, the manual marriage registration process often leads to challenges such as delays in processing, lack of data transparency, and potential administrative errors. To address these issues, a web-based marriage registration information system was developed with the aim of creating a marriage registration information system that can assist the public in conducting marriage registrations and help the KUA in managing and retrieving marriage registration data online. This system aims to reduce processing time and benefit the KUA in managing registration data and searching for data more quickly. The marriage registration information system at Semidang Alas Sub-district KUA can be accessed online via the registered link https://daftarnikahkuasemidang.online/. The method used in this study is a qualitative approach with data collection techniques through observation, interviews, and documentation studies. The system development was carried out using the Rapid Application Development (RAD) method, which consists of the stages of needs analysis, system design, implementation, testing, and maintenance. The technologies used include PHP and MySQL. The results of the study indicate that web-based marriage registration information system developed is capable of accelerating administrative processes, minimizing data errors, and providing easy access for prospective brides and grooms as well as KUA officials. This system can also generate reports automatically, thereby facilitating the reporting and archiving of data. With this information system, it is hoped that public services in the KUA environment will become more modern, efficient, and transparent.